Implementation of Da'wah Activity Supervision at Pondok Pesantren Subulussalam - Abi Rabsanjani; Aya Ghina Alfarah; Muhammad Zeva Noer Ikhsan Ikhsan; Siti Nurhalisa (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Supervision or controlling is one of the essential functions in management that aims to ensure that the plans that have been made are running in accordance with the set targets. In this context, supervision focuses not only on evaluating the success of activities in achieving goals, but also on identifying and correcting errors that may occur during the process. In addition, supervision plays an important role in providing solutions to problems that arise, so that the organization can stay on the right track. In this study, the function of supervision is also linked to the role of the mass media, which serves as a provider of information and notification to the public regarding developments around it. Through supervision, up-to-date information can be gathered to broaden the understanding of the organization and its context. This research focuses on the implementation of supervision of da'wah activities at Subulussallam, with the aim of analyzing the effectiveness of supervision in achieving da'wah goals and improving the quality of activities carried out. The results of this study are expected to provide deeper insight into the importance of supervision in the management of da'wah activities in the pesantren environment.